2001
DOI: 10.1002/jbm.1061
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of canine peroneal nerve with the use of a polyglycolic acid–collagen tube filled with laminin‐soaked collagen sponge: a comparative study of collagen sponge and collagen fibers as filling materials for nerve conduits

Abstract: A novel artificial nerve conduit was developed and its efficiency was evaluated on the basis of promotion of peripheral nerve regeneration across an 80-mm gap in dogs. The nerve conduit was made of a polyglycolic acid-collagen tube filled with laminin-soaked collagen sponge. Conduits filled with either sponge- or fiber-form collagen were implanted into an 80-mm gap of the peroneal nerve (five dogs for each form). Twelve months postoperatively nerve regeneration was superior in the sponge group both morphometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 43 publications
2
68
0
3
Order By: Relevance
“…Other ECM molecules, such as collagen and fibronectin, have the ability to significantly increase SC adhesion as well as proliferation, and enhance neurite outgrowth however, although results have been shown to be significantly lower than that of laminin [13,73,74]. A number of studies have conjugated laminin to their respective material or used them to enhance the aforementioned intraluminal fillers [36,46,68,70,76]. Each respective study notably showed a significant increase in nerve regeneration compared with that of uncoated fibres [36,46,68,70].…”
Section: Surface Modifications and Peptide Mimeticsmentioning
confidence: 99%
“…Other ECM molecules, such as collagen and fibronectin, have the ability to significantly increase SC adhesion as well as proliferation, and enhance neurite outgrowth however, although results have been shown to be significantly lower than that of laminin [13,73,74]. A number of studies have conjugated laminin to their respective material or used them to enhance the aforementioned intraluminal fillers [36,46,68,70,76]. Each respective study notably showed a significant increase in nerve regeneration compared with that of uncoated fibres [36,46,68,70].…”
Section: Surface Modifications and Peptide Mimeticsmentioning
confidence: 99%
“…Substantially larger segmental defects could be reconstructed, and the morbidity of harvesting would be eliminated. Several types of materials have been proposed as peripheral nerve substitutes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], including autologous materials such as vein and muscle strips, synthetic materials such as polylactic acid and polyglycolic acid, non-autologous biological materials such as acellular peripheral nerve allograft, and conduits made of collagen, laminin, fibronectin, and alginate.…”
Section: Introductionmentioning
confidence: 99%
“…Toba et al 42 developed a novel nerve conduit composed of polyglycolic acid (PGA)-collagen tube filled with human LM (10g/ ml) soaked collagen sponge that was implanted into an 80-mm gap of peroneal nerve in dogs. At 12months post-surgery, the conduit was completely absorbed and a high density of myelinated axons could be observed in the regenerated nerve segment.…”
Section: Peripheral Nervous System Regenerationmentioning
confidence: 99%